2021
DOI: 10.3390/ijms22147635
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TRPM2 in Endothelial Function and Dysfunction

Abstract: The transient receptor potential (TRP) melastatin-like subfamily member 2 (TRPM2) is a non-selective calcium-permeable cation channel. It is expressed by many mammalian tissues, including bone marrow, spleen, lungs, heart, liver, neutrophils, and endothelial cells. The best-known mechanism of TRPM2 activation is related to the binding of ADP-ribose to the nudix-box sequence motif (NUDT9-H) in the C-terminal domain of the channel. In cells, the production of ADP-ribose is a result of increased oxidative stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The main mechanism of oxidative stress-induced cell damage is to disrupt intracellular ion homeostasis. TRPM2 is a calcium ion-permeable cation channel that is activated in response to oxidative stress, whereby resulting in the increase in calcium influx in endothelial cells and further causing endothelial dysfunction [ 53 , 54 , 55 ]. Meanwhile, TRPM2 may be involved in high-glucose-induced mitochondrial fission in endothelial cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanism of oxidative stress-induced cell damage is to disrupt intracellular ion homeostasis. TRPM2 is a calcium ion-permeable cation channel that is activated in response to oxidative stress, whereby resulting in the increase in calcium influx in endothelial cells and further causing endothelial dysfunction [ 53 , 54 , 55 ]. Meanwhile, TRPM2 may be involved in high-glucose-induced mitochondrial fission in endothelial cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, TRPM2 channels are expressed in the lung endothelium and participate in the regulation of barrier function [ 150 , 151 ], cell death, migration and angiogenesis (reviewed in [ 152 ]). Vascular endothelial growth factor (VEGF) in endothelial cells drives their migration, proliferation, and disassembly of adherens junctions, as well as the production of reactive oxygen species (ROS), which activate TRPM2 channels [ 152 ].…”
Section: Roles For Trp Channels In Barrier Function Of the Pulmonary ...mentioning
confidence: 99%
“…As outlined above, TRPM2 channels are expressed in the lung endothelium and participate in the regulation of barrier function [ 150 , 151 ], cell death, migration and angiogenesis (reviewed in [ 152 ]). Vascular endothelial growth factor (VEGF) in endothelial cells drives their migration, proliferation, and disassembly of adherens junctions, as well as the production of reactive oxygen species (ROS), which activate TRPM2 channels [ 152 ]. Importantly, the deletion of endothelial TRPM2 channels reduce the transendothelial migration of polymorphonuclear neutrophils, which produce ROS in response to LPS from Gram-negative bacterial membranes in the circulating blood of the pulmonary vasculature [ 153 ].…”
Section: Roles For Trp Channels In Barrier Function Of the Pulmonary ...mentioning
confidence: 99%
“…Studies have shown that S100 proteins play a role in chemotaxis and activation of immune cells in relationship with OS process and transient receptor potential (TRP). In endothelial cells, specific members of the TRP superfamily of cation channels act as important Ca 2+ influx pathways [ 44 ]. They are involved in endothelium-dependent vasodilation and regulation of permeability and angiogenesis.…”
Section: Calprotectin Oxidative Stress and Redox Potentialmentioning
confidence: 99%